The effects of textured insoles on quiet standing balance in four stance types with and without vision - Ryan P. W. Kenny; Daniel L. Eaves; Denis Martin; Anna L. Hatton; John Dixon (BMC, 2019)
Abstract Background Wearing a textured shoe insole can decrease postural sway during static balance. Previous studies assessed bipedal and/or unipedal standing. In contrast, we aimed to investigate if textured insoles modulated postural sway during four stance types (bipedal, standard Romberg, tandem Romberg, and unipedal), with and without vision. Methods The repeated measures design involved 28 healthy young adults (13 females; mean age = 26.86 ± 6.6 yrs) performing quiet standing in the four stance types on a force platform, under two different insole conditions (textured insole; TI vs. smooth insole; SI), with eyes open and eyes closed. Postural sway was assessed via the range and standard deviation of the COP excursions in the anterior-posterior and medial-lateral sway, and overall mean velocity. Results The main effect of insole type was statistically significant at the alpha p = 0.05 level (p = 0.045). Compared to smooth insoles, textured insoles reduced the standard deviation of anterior-posterior excursions (APSD). While simple main effect analyses revealed this was most pronounced during eyes closed bipedal standing, insole type did not provide a statistically significant interaction with either stance or vision in this measure, or any other. Postural sway showed statistically significant increases across both stance type (bipedal < standard Romberg < tandem Romberg < unipedal), and vision (eyes closed < eyes open), in almost all measures. Stance and vision did have a statistically significant interaction in each measure, reflecting greater postural disturbances with eyes closed when stance stability decreased. Conclusions Overall, these results support textured insole use in healthy young adults to reduce postural sway measures. This is because APSD is an index of spatial variability, where a decrease is associated with improved balance and possibly translates to reduced falls risk. Placing a novel texture in the shoe presumably modulated somatosensory inputs. It is important to understand the underlying mechanisms by which textured insoles influence postural sway. As such, utilising a healthy adult group allows us to investigate possible mechanisms of textured insoles. Future research could investigate the potential underlying mechanisms of textured insole effects at a neuromuscular and cortical level, in healthy young adults.